2006
DOI: 10.1002/pssa.200669591
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of thermoelectric properties in (Pr,Y)Ba2Cu3O7 and PrBa2Cu3O7–Ag percolative systems

Abstract: PACS 72. 74.25.Fy, 74.72.Bk Measurements of the temperature-dependent thermoelectric power S(T) and resistivity ρ(T) were performed to characterize two kinds of polycrystalline systems (Pr 1-x Y x )Ba 2 Cu 3 O 7 and Ag-doped PrBa 2 Cu 3 O 7 , each of which exhibits percolative behaviour at a certain doping level. At room temperature, Jonker plots of the thermoelectric power against logarithm of the conductivity in both systems show a similar tendency that two different fitting lines are intercrossed at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…(1) and (2), though ICO films are not exactly nondegenerated semiconductors. We have already reported that similar results are observable in thermoelectric properties of percolative oxide systems[15]. From the least squared fits (LSF) to the data (the solid lines), we obtain experimental values a = 228 and 282 µV/K for Eqs (1).…”
supporting
confidence: 71%
See 3 more Smart Citations
“…(1) and (2), though ICO films are not exactly nondegenerated semiconductors. We have already reported that similar results are observable in thermoelectric properties of percolative oxide systems[15]. From the least squared fits (LSF) to the data (the solid lines), we obtain experimental values a = 228 and 282 µV/K for Eqs (1).…”
supporting
confidence: 71%
“…Results for the analyses of S(T ) data are displayed in Fig. 4(a) for the cases of Nd 2−y Ce y O 4 (NCCO) [14] and Ag-doped PrBa 2 Cu 3 O 7 (Pr-Ag) [15] which are known as electrondoped (n-type) and hole-doped (p-type) materials, respectively. In the former system, Ce was substituted for Nd in the atomic ratio y (at.%) while Ag was added in the volume fraction z (vol.%) in the latter one.…”
Section: Related Results For S(t ) In Bulk Ceramicsmentioning
confidence: 99%
See 2 more Smart Citations